Graduate Students of Color: Race, Racism, and Mentoring in the White Waters of Academia. Issue 1 (January 2017) - Brunsma, David L.; Embrick, David G.; Shin, Jean H.
The graduate student experience, for many, can be a time of great stress, insecurity, and uncertainty. Overwhelmingly, studies verify that good mentoring is one of the best indicators of graduate student success. In this literature review, we outline in detail previous research that attest to these experiences, and pay specific attention to the experiences of students of color. In general, our read of the literature suggests that academia, in general, and sociology, in particular, does not do a good job of mentoring graduate students of color. We begin our essay with an overview of graduate student experiences. Next, we discuss the mentoring side of the equation, addressing reasons that might explain variations in how students are mentored in higher education. Finally, we end with some thoughts on what faculty and departments can do to address the inadequate mentoring of graduate students of color.